An Evaluation of Tertiary Educators’ Perception of Online Teaching Related Ergonomic Factors - Ghosh, Mitali (Curtin University, 2024)
The Aim of this research was to identify and assess ergonomic factors that affected educators in minerals, mining engineering and other educators’ experience with online teaching. Noise, insufficient time to complete all teaching related work, and lack of interaction with students were the main barriers identified. There was minimal difference in factors between minerals, mining engineering, and other educators’ experiences. Having good physical, organisational, cognitive, social, and environmental ergonomic factors facilitated online educators’ work.